COLON OXALATE-DEGRADING BACTERIA COLONIZATION IN PATIENTS WITH RECURRENT PYELONEPHRITIS AND ITS RELATIONSHIP WITH ADMINISTRATION OF ANTIBIOTICS (PILOT STUDY) - N. Dzyubenko; N. Stashevska; G. Tolstanova; T. Sergiychuk; I. Akulenko; N. Stepanova (Український Журнал Нефрології та Діалізу, 2016)
Antibiotic therapy and long-term antibiotic prophylaxis affect the normal flora of the gastrointestinal tract in the patients with recurrent pyelonephritis. It may disturb the balance in oxalate-degrading bacteria in colon and induce hyperoxaluria.